Stigma Association Type and Sponsor Corporate Image: Exploring the Negative Off-field Behaviour of Sportspeople. Issue 4 (November 2020) - Bloxsome, Ellen; Brown, Mark; Pope, Nigel; Joseph, Christopher
This paper examines how consumers' exposure to news-media reports of an athlete's negative off-field behaviour influences perceptions of a sporting team's sponsor. Stigma-by-association is proposed as an explanatory theory for the manner in which this process occurs. Two experiments were conducted on samples of both students and adults. Results indicate that off-field behaviour of athletes has no influence on consumer perceptions of sponsor corporate image under conditions of simple association. In contrast, significant changes in sponsor corporate image are found under meaningful association conditions. The results provide an understanding of how consumers make differential attribution judgments of associated entities dependent on the context of off-field behaviour. The research highlights implications for sponsors seeking to maximise the effectiveness of their sponsorship objectives.